2009
DOI: 10.5539/ijms.v1n1p66
|View full text |Cite
|
Sign up to set email alerts
|

Retaining Customers through Relationship Marketing in an Islamic Financial Institution in Malaysia

Abstract: Questions on ways to retain loyal customers and attract potential future customers in an Islamic financial institution led to a study on customer relationship marketing (CRM) strategies at the Pilgrims Fund Corporation or Tabung Haji (TH). This study aims to determine whether customer relationship marketing (CRM) influenced by the variables -customers' satisfaction, employees' commitment, customers' trust and customers' loyalty. Questionnaires and personal interviews with the respondents were used. 152 registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…Relationship marketing and customer retention: This finding is similar with what Kassim et al (2009) and Liang et al (2008) have found. Relationship Marketing is a popular concept in current marketing research and practice; it has the potential to increase customer retention by building long-term customer relationships (Wang and Head, 2005).…”
Section: Discussion and Recommendations 51 Discussion Of The Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…Relationship marketing and customer retention: This finding is similar with what Kassim et al (2009) and Liang et al (2008) have found. Relationship Marketing is a popular concept in current marketing research and practice; it has the potential to increase customer retention by building long-term customer relationships (Wang and Head, 2005).…”
Section: Discussion and Recommendations 51 Discussion Of The Findingssupporting
confidence: 89%
“…Hougaard and Bjerre (2002) defines it as a company behavior with the purpose of establishing, maintaining and developing competitive and profitable customer relationships to the benefit both parties. Kassim, Bahari and Kassim, (2009) defined it as a company's activity that helps in developing and retaining customers through increased loyalty, satisfaction, trust and commitment.…”
Section: Relationship Marketingmentioning
confidence: 99%
“…The research was conducted by (Kassim et al, 2009), the final conclusion of this study is (1) There is a positive influence between service quality and customer satisfaction, amounting to 0.659, (2) There is a positive influence between service quality and consumer trust, amounting to 0.731 (3) There is a positive influence between satisfaction and trust, amounting to 0.731 (4) There is a positive influence between customer satisfaction and loyalty, amounting to 0.386 (5) There is a positive influence between customer trust and loyalty, amounting to 0.509. From the results of this study, the loyalty of executive railroad users can be formed, if the quality of services around the station and inside the railroad car can provide user satisfaction.…”
Section: Influence Perception Of Service Quality On Satisfactionmentioning
confidence: 99%
“…Relationship Marketing involves "two-way communication" and accentuates "strong personal relations, interaction and social exchange in order to succeed" (Chen, et al, 2008). Kassim et al (2009) defined it as a company"s activity that helps in developing and retaining customers through increased satisfaction, trust, loyalty, and commitment.…”
Section: Relationship Marketing (Rm)mentioning
confidence: 99%